FEATURES OF CHANGE OF HYDROCHEMICAL MODE OF THE RIVER IKVA UNDER THE ANTROPOGENIC ACTIVITY - Klуmenko Mykola; Pryschepa, Alla; Statnуk Ihor; Biedunkova, Olha; Budnik, Zinaida (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
In the article an analysis of the basic hydrochemical parameters of the river Ikva for 2001–2016 years is conducted. The change of hydrochemical parameters under the influence of anthropogenic activity is characterized and the main factors of influence on the Ikva river basin are determined.